Reliability of the Expanded Cutting Alignment Scoring Tool (E-CAST) to Assess Trunk and Limb Alignment During a 45-Degree Side-Step Cut - Lauren S. Butler; Alexa R. Martinez; Dai Sugimoto; Charles W. Wyatt; Eryn K. Milian; Sophia Ulman; Ashley Erdman; Alex Loewen; Kristin Hayden; Amie DeVerna; Kirsten Tulchin-Francis; PRiSM Injury Prevention Research Interest Group (International Journal of Sports Physical Therapy)
# Background